A new treatment approach to conduct disorder and callous-unemotional traits: an assessment of the acceptability, appropriateness, and feasibility of Impact VR - Thomson, Nicholas D.; Kevorkian, Salpi S.; Hazlett, Laura; Perera, Robert; Vrana, Scott (Frontiers in Psychiatry, 2025)
IntroductionConduct disorder (CD) is highly prevalent among youth, yet existing and conventional treatment approaches are limited and costly. Further, most interventions for CD focus on behavior management rather than targeting the underlying mechanisms of CD. To meet the needs of youth with CD (ages 10-17), we developed Impact VR, a virtual reality intervention that promotes competency in emotion recognition and regulation, as well as modeling prosocial behaviors. Impact VR provides immersive storylines and gamification of psychoeducation training. The present study aimed to understand the perceptions of Impact VR for acceptability, feasibility, and usability across key stakeholder groups, including youth with CD, caregivers of youth with CD, mental health practitioners, and educators.MethodsA total of 60 adults, including mental health professionals (n=20), teachers (n=20), caregivers (n=20), and 20 youth with CD completed a trial of Impact VR and completed surveys.ResultsResults demonstrated a high overall acceptability of Impact VR (95% - 100%) across all groups, and a high approval rating for intervention appropriateness (98.75% - 100%) and feasibility of the intervention (97.50% - 100%) across stakeholder groups. The majority of youth (90%-100%) reported that the skills learned would improve their mental health and relationships with friends, parents, and teachers.DiscussionFindings revealed that youth with CD and key stakeholder groups rate Impact VR favorably and positively. Future research is needed on the effectiveness of Impact VR in improving emotion recognition and reducing CD symptoms.